Experimental Investigation of sample preparation and grouting technology on microbially reinforced tailings. (20th December 2021) - Lu, Ting; Wei, Zuoan; Wang, Wensong; Yang, Yonghao; Cao, Guansen; Wang, Ya; Liao, Haidong
Highlights: The raw material is fine-grained phosphate tailings. Propose an innovative method for reinforcing fine-grained geotechnical materials. The mechanism of MICP reinforces tailings is connection and wrapping. Mixing method can avoid the nonuniformity of samples in reinforcement treatment. Abstract: The nonuniformity of samples in reinforcement treatment is a bottleneck that restricts the development of microbial geotechnical technologies, which severely affects the reinforcement effect of microbially reinforced tailings and other fine-grained geotechnical materials. This study presents a mixing method that represents an innovative sample preparation and grouting technology for reinforcing tailings using microbially induced calcite precipitation (MICP) based on the characteristics of tailings discharged in the form of mud and accumulated layer-by-layer. A large number of mechanical experiments and microanalyses were conducted to compare the effects of various methods on tailings reinforcement, including the methods of adding bacterial solution (i.e., the traditional grouting method and the proposed mixing method) and the treatment methods of cementing solution (i.e., the grouting method and soaking). The results of the shear test showed that the strength of the samples generated by the mixing method increased compared with the original tailings samples and samples generated using the traditional grouting method. Moreover, miniature cone penetration test results showed that the samples made using the mixing method had better uniformity, which could be attributed to the fine particles (silt and clay particles) of tailings that strongly adsorb bacteria and the low permeability of the fine particle tailings, which is not conducive to the spread of bacteria. In the tailings samples, the traditional grouting method only makes the bacteria gather at the region where the bacterial solution initially makes contact. However, the mixing method evenly distributed the bacteria among the tailings particles, which significantly improved the reinforcement effect of bacteria, as the reinforcement reaction occurred throughout each region of the samples. Therefore, the mixing method can be used for reinforcement research and in the application of MICP to tailings or other fine-grained geotechnical materials.